2017
DOI: 10.1002/anie.201701533
|View full text |Cite
|
Sign up to set email alerts
|

Trimetallic Oxyhydroxide Coralloids for Efficient Oxygen Evolution Electrocatalysis

Abstract: Trimetallic oxyhydroxides are one of the most effective materials for oxygen evolution reaction (OER) catalysis, a key process for water splitting. Herein, we describe a facile wet-chemical method to directly grow a series of coralloid trimetallic oxyhydroxides on arbitrary substrates such as nickel foam (NF) and carbon nanotubes (CNTs). The amount of iron in these oxyhydroxide sponges on NF and CNTs was precisely controlled, revealing that the electrocatalytic activity of the WCoFe trimetallic oxyhydroxides d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
135
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(136 citation statements)
references
References 65 publications
1
135
0
Order By: Relevance
“…Electrochemical impedance spectroscopy was further used to characterize the OER kinetics. [22] The reduced semicircular diameter in Nyquist plots compared to the ternary ones and commercial Ir/C catalysts ( Figure S7, Supporting Information) reveals charge-transfer resistance reduction when both Co and Fe are incorporated into the nanoparticles. [20,23] We investigated the electrochemical double-layer capacitance, which is proportional to the electrochemically active surface area (ECSA).…”
Section: Resultsmentioning
confidence: 99%
“…Electrochemical impedance spectroscopy was further used to characterize the OER kinetics. [22] The reduced semicircular diameter in Nyquist plots compared to the ternary ones and commercial Ir/C catalysts ( Figure S7, Supporting Information) reveals charge-transfer resistance reduction when both Co and Fe are incorporated into the nanoparticles. [20,23] We investigated the electrochemical double-layer capacitance, which is proportional to the electrochemically active surface area (ECSA).…”
Section: Resultsmentioning
confidence: 99%
“…In general, elemental doping can increase site activities through the formation of defect sites, the enhancement of electronic conductivities, and the modification of intrinsic electronic structures of catalysts, resulting in lowered energy barriers …”
Section: Approaches To Enhancing the Activitymentioning
confidence: 99%
“…[20] Generally,r educing the size of catalysts to offer more active sites, and compositing with 3D carbonous or metallic frameworks to enhance the electronic conductivity and mass diffusion simultaneously are efficient methods to improve the electrochemical activity of catalysts. [25,26] Thei ncorporation of heteroatoms [27,28] is also capable of creating more active sites and/or adjusting their electron configuration to obtain preferable OER catalytic performance.B esides,P etrie et al [29] found that strain-induced e g orbital splitting and polarization enhance the activity of LaNiO 3 for promoting active centers at asymmetric surfaces. [25,26] Thei ncorporation of heteroatoms [27,28] is also capable of creating more active sites and/or adjusting their electron configuration to obtain preferable OER catalytic performance.B esides,P etrie et al [29] found that strain-induced e g orbital splitting and polarization enhance the activity of LaNiO 3 for promoting active centers at asymmetric surfaces.…”
Section: Introductionmentioning
confidence: 99%